The Smart Grid Challenge is Social Rather than Technological - Donato, Patricio G.; Funes, Marcos A. (Current Engineering Letters and Reviews, 2024)
BackgroundSmart grids have expanded over the last decade, with large-scale smart meter deployments in several regions of the world.ObjectiveThe goal of this perspective is to discuss the social challenges faced by smart grids. While numerous scholarly works have thoroughly examined smart grids from a technical perspective, a noticeable shift has occurred in recent years towards conducting research about the interaction between technology and customers that shows some issues to future deployments.MethodsThis study is a review of recent literature on smart grids focused on studies related to the social acceptance of these networks, which has been published in the last five years.ResultsThe review of studies shows that discussion about smart grids has been traditionally focused on technology, paying no attention to social issues.ConclusionIt is essential to understand the motivations behind public perceptions of smart grids in order to enhance and extend awareness campaigns in the short and medium term, as without social support, the expectations placed on smart grids may be severely limited.
Keywords: smart metering